Proyecto de inversión de un buque pesquero para optimizar la capacidad productiva de agrol s.a. - García Cedeño, Lissette Nataly (2010)
This study shows the feasibility analysis for implementing the investment project of a fishing vessel to optimize the productive capacity of Agrol SA, headquartered in the largest fishing port of Ecuador, Manta. For this study, we have been implemented the projection of demand, financial analysis using various indicators and collection of information, to thereby direct import processes and nationalization of the new fixed assets of the company, covering high requirements and demands of local and international markets, ranging from the capture phase, processing and marketing of tuna. For this, we applied relevant studies, based on primary and secondary requirements, on the other hand were estimated production technician to determine the optimal infrastructure of the plant, industry analysis, in order to determine the economic viability, legal and productive. In order to generate a different and innovative business option for investors, in an industry that is currently in growth phase, which in turn will allow us to generate new sources of direct and indirect employment.